Climate change and coastal archaeology in the Middle East and North Africa: assessing past impacts and future threats. (3rd April 2023) - Westley, Kieran; Andreou, Georgia; El Safadi, Crystal; Huigens, Harmen O.; Nikolaus, Julia; Ortiz-Vazquez, Rodrigo; Ray, Nick; Smith, Ash; Tews, Sophie; Blue, Lucy; Breen, Colin
Abstract: Climate change threatens coastal archaeology through storm flooding (extreme sea-level: ESL), long-term sea-level rise (SLR) and coastal erosion. Many regions, like the Middle East and North Africa (MENA), lack key baseline evidence. We present initial results from a climate change threat assessment of MENA's coastal heritage using the Maritime Endangered Archaeology inventory: a geospatial database of MENA maritime archaeological sites incorporating a disturbance/ threat assessment. It informs two analyses of past disturbance and future threat: (1) using the integral threat/disturbance assessment, and (2) geospatial extraction of information from external coastal change models. Analysis suggests <5% of documented coastal sites are definitely affected by coastal erosion but up to 34% could also have experienced past flooding, erosion, or storm action. Climate change-related threats will increase over the 21st Century and accelerate post-2050 if carbon emissions remain high. SLR and ESL could impact 14–25% of sites by 2050 and 18–34% by 2100. Over 30% to 40% of sites could be impacted by erosion by 2050 and 2100 respectively. Whilst documentation is ongoing and there remain modeling uncertainties, this approach provides a means to redress the absence of baseline data on climate change threats to coastal cultural heritage in MENA .